Loss of the F-Actin Binding and Vesicle-Associated Protein Comitin Leads to a Phagocytosis Defect - Schreiner, Thomas (American Society for Microbiology, 2002)
Comitin is an F-actin binding and membrane-associated protein from Dictyostelium discoideum, which is present on Golgi and vesicle membranes and changes its localization in response to agents affecting the cytoskeleton. To investigate its in vivo functions we have generated knockout mutants by gene replacement. Based on comitin's in vitro functions we examined properties related to vesicular transport and microfilament function. Whereas cell growth, pinocytosis, secretion, chemotaxis, motility, and development were unaltered, comitin-lacking cells were impaired in the early steps of phagocytosis of Saccharomyces cerevisiae particles and of Escherichia coli, whereas uptake of latex beads was unaffected. Furthermore, the lack of comitin positively affected survival of pathogenic bacteria. Mutant cells also showed an altered response to hyperosmotic shock in comparison to the wild type. The redistribution of comitin during hyperosmotic shock in wild-type cells and its presence on early phagosomes suggest a direct involvement of comitin in these processes.